Industrial Accidents as Corporate Crimes: An Analysis of PT ASL Shipyard Batam's Liability under Indonesia’s National Criminal Code - Cut Wahidah Mumtaza; Parningotan Malau (Dinasti Research, 2026)
Industrial accidents resulting in worker fatalities continue to be a substantial concern in Indonesia's labour sector. Notwithstanding the enactment of various occupational safety and health regulations, the attribution of criminal guilt in cases of fatal workplace accidents continues to be contentious, especially regarding the classification of enterprises as entities subject to criminal law. This circumstance creates a discrepancy between the occupational safety obligations imposed on companies and the penalties enforced when violations of these obligations lead to worker fatalities. This study aims to assess the legal qualifications of the explosion incident at PT ASL Shipyard Batam, evaluate the adequacy of Law Number 1 of 1970 concerning Occupational Safety in determining corporate criminal liability, and examine the framework of corporate criminal liability and management in accordance with the National Criminal Code. The research utilises a normative legal technique, incorporating both legislation and case analyses. The study's findings suggest that the explosion at the MT Federal II PT ASL Shipyard Batam, which led to worker fatalities, could be deemed a criminal offence if negligence in safety compliance is proven. Law Number 1 of 1970 remains relevant as the basis for regulating occupational safety responsibilities; however, it is inadequate for establishing corporate criminal liability, as it does not recognise corporations as entities under criminal law or provide a framework for attributing corporate culpability. In contrast, the National Criminal Code, through Articles 45 to 49, delineates a normative framework that allows for the imposition of criminal liability on both corporations as entities and on administrators in functional roles, order issuers, control holders, and beneficial owners of corporations. This study established that worker fatalities from industrial accidents are not exclusively due to the company's operational hazards; instead, they may constitute a basis for corporate criminal liability if systemic negligence in enforcing and overseeing occupational safety standards is demonstrated.